A CLINICAL STUDY TO EVALUATE THE EFFICACY OF KASHMARYADI OIL (TRADITIONAL FORMULA) IN THE MANAGEMENT OF KHALITYA - MPN, Pramodani; KPP, Peiris (International Journal of Research -GRANTHAALAYAH, 2017)
Hair loss is a dermatological disorder that has been recognized for more than 2000 years. It is common throughout the world and has been estimated to affect nearly 2% of the world's population. Apart from metabolic and hereditary causes, alopecia has been observed as a major side effect of anticancer, immunosuppressant and many others drug treatments. To solve the above query and to find out a promising remedy, the present study has been undertaken. In Ayurvedic approach, loss of hair is coined out as in term of Khalitya under the broad heading of Shiroroga. For this Moordha Taila (Shiroabyanga) is the management and when is done with Taila which is medicated by hair growing drugs is more efficacious. So in present study Kashmaryadi oil advocated in traditional medicine that has Keshya properties has been selected. Sixty patients were selected; they were examined and recorded their history in the performa that prepared including all the necessary aspects of Ayurveda and modern medical science. The patients were advised to give gentle massage to the scalp covering whole area with hair oil at night and rinse it in the morning. The clinical condition was assessed before, after two weeks, after four weeks and after follow up period. Using grading system assessed signs and symptoms. Hair fall, Darunaka, Kandu, Kesha Rukshatwa, Kesha Katinya, Kesha Tanutwa, Kesha Bhoomi Daha, Kesha Bhoomi Durganda were assessed and observed the significant reduction of symptoms. Considering the total treatment assessment there were 41.67% complete remission, 30% marked improvement, 16.67% moderate improvement, 8.33% mild improvement and 3.33% unchanged. No adverse reaction reported in this study period. It is concluded that Kashmaryadi oil is very effective in the treatment of hair loss.